Cry me a Pele’s tear: new insights on the internal structures of Pele’s tears - Moyer, Scott; Sahagian, Dork (Frontiers in Earth Science, 2023)
In this paper we present novel observations of internal structures of Pele’s tears and spheres revealed from SEM studies of particles formed within Kilauean lava fountains. Partially weathered Pele’s tears from eruption episodes in 1969 include a crust, or rind, of material that is smooth on the external surface. However, once this crust is peeled away, it reveals a sub-crustal surface within the tear that is morphologically complex. This surface is characterized by a network of ridges and valleys that warp around radial structures with pores at their centers. The ridges and valleys are interpreted to represent the differential cooling and shrinkage of the external surface of the spheres and tears relative to the interior upon exiting the lava fountain and chilling in ambient air. The radial structures are interpreted to be formed as result of chemical zonation within the cooling at locations where a vesicle contacts the external crust. An additional feature is observed on the underside of crust that is peeled off each tear. This surface has a roughly polygonal network of tubes that surround pores at the center of many of the polygons. The tubes are hollow and some contain solid material within, possibly the remains of the crushed top of the tube where the SEM can peer inside. The origin of this tube network is a puzzle remaining to be solved.